Autonomous station for recording radiation in a thunderstorm atmoshere at the Tien Shan high mountain cosmic-ray station - Shaulov, S.B.; Saduyev, N.O.; Kalikulov, O.A.; Zhukov, V.V.; Ryabov, V.A.; Shepetov, A.L.; Vil’danova, V.I.; Yerezhep, N.; Muhkamejanov, E.S.; Shinbulatov, S.K.; Zhumabayev, A.I.; Utey, Sh.B. (Recent Contributions to Physics, 2019)
During the past decades, considerable attention has been paid to the search and registration of electromagnetic radiation accompanying lightning discharges in the atmosphere when studying processes occurring in thunderclouds. Such studies are of interest for understanding the mechanisms of lightning generation and its further development, leading to the generation of an avalanche of charged particles accelerated by an electric field, the hard bremsstrahlung of which is registered by the detectors. In this work we consider a compact measuring system, which was created at the Tien Shan High-Mountain Scientific Station for registering radiation during thunderstorm activity. A feature of the system is complete autonomy, when all its components (detectors, recording electronics, battery) are placed inside a solid metal casing, which plays the role of an electromagnetic screen and does not have any connections to external cable lines. This allows one to record radiation directly inside the thundercloud. Examples of gamma-radiation detection using a NaI crystal scintillation detector, as well as the detection of charged particles by a special detector, which is a stack of two flat scintillation detectors of a large area and a rubber filter placed between them, are considered.